(untitled) (Annals of Medical Research, 2021)
Aim: In this study, naringin was examined against injuries in lung and ovarian tissues caused by ovarian torsion/detorsion (T/D). Material and Methods: The animals were grouped as sham, T/D, 50 mg/kg Naringin and 100 mg/kg Naringin. In sham group, the abdomen was incised and then sutured but T/D model wasn’t performed. In T/D group, torsion and detorsion (ischemia 3 hours/reperfusion 3 hours) were carried out. In naringin treatment groups, naringin was applied intraperitoneally at the doses of 50 and 100 mg/kg about 30 minutes prior to detorsion. After detorsion period, experimental animals were immolated and the ovarian and lung tissues were excised, homogenized and the biochemical analyzes were done. Results: The activity of MPO, IL-1β, MDA, TNF-α levels, TOS and OSI parameters raised significantly but SOD activity and TAS values declined in T/D group when it is compared to sham group. On the other side, naringin treatments reversed these parameters.Conclusion: Thereby, naringin demonstrated therapeutic effect against the injuries of ovarian and lung tissues in rat T/D model.